Influencia de la relación pasta de maní/pollo en la calidad fisicoquímica, nutricional y microbiológica de un chorizo - Álvarez Cevallos, Luis Jordano (2024)
The objective of this research was to evaluate the effect of the ratio of peanut paste (Arachis hypogaea) and chicken as a substitute for pork fat on the physicochemical, nutritional, microbiological and sensory properties of a chorizo. Four treatments were designed with different concentrations of peanut and chicken paste (20%-60%, 15%-65%, 10%-70%, 5%-75%). The physicochemical quality (pH, Acidity, Oxidative stability), nutritional content (protein, fat) and microbiological analysis (Salmonella, E. Coli, Mesophilic Aerobes) were evaluated, which were contrasted with the Ecuadorian regulations NTE INEN 1338. A Unifactorial Design was applied. Completely Randomized (DCA) with three repetitions for each treatment. The results of the nutritional analysis showed a significant increase in protein content and a decrease in fat as the amount of peanut paste decreased and the amount of chicken in the chorizo increased. With respect to the microbiological analyzes, treatments T1 (20%-60% peanut paste/chicken ratio) and T2 (15%-65% peanut paste/chicken ratio) met the standards established by NTE INEN 1338:2012 for E.Coli, A. Mesophiles and absence of Salmonella. However, treatments T3 (10%-70% peanut paste/chicken ratio) and T4 (5%-75% peanut paste/chicken ratio) showed the presence of E. Coli and A. Mesophiles, therefore it was not possible to carry out the sensory test in order to preserve the health of the tasters. The treatment that presented the best conditions in all variables except protein was T1 (20%-60% peanut paste/chicken ratio).